Coesão e coerência em editorial de jornal: uma perspectiva sistêmico-funcional - Sousa, Eliane Alves de (2012)
The objective of this research is to examine cohesion and coherence in editorials of newspapers, checking the lexico-grammatical choices that are made for their realization. Methodologically, the research is based on Halliday s (1985, 1994) Systemic Functional Linguistics (LSF), and on his collaborators. unity is the most important feature of the text, says Hasan (1989), scholar of LSF. It is unity that enables us to distinguish a text from a non text, a complete text, from an incomplete one. There are two kinds of unity: structure unity and texture unity. The property texture or cohesion is related to the perception of the coherence by the reader. This relationship between cohesion and coherence has in Eggins (1994), a systemicist an explanation that I consider quite enlightening. Thus, a text can be coherent in terms of: (a) cultural, if it presents genre structure with its stages and purposes, and (b) situational, if it respects Register rules - through Field, Tenor and Mood variables. Now, a text will be cohesive if: (a) it keeps its participants; (b) if it observes proper lexical selection; and (c) if it uses conjunctions (in this I include the speeches markers) to relate the clauses. Eggins speaks of four types of textual cohesion: (1) referential, (2) lexical, (3) conjunction and (4) conversational structure (this last will be not considered in this research, since I am not analyzing converse). For coherence and cohesion to happen, I also bring the concept of Appraisal (MARTIN, 2000, 2003), broadened by the proposal of cohesion realized by prosody: the attitudinal meaning that extends through the text and links parts of the text through evaluations related among themselves. (LEMKE, 1998). This research should answer the following questions: (i) How is coherence and cohesion realized in the newspaper editorials examined? (ii)Which lexical-grammatical choices realize coherence and cohesion in a newspaper editorial?